Design and antimicrobial activities of LL‐37 derivatives inhibiting the formation of Streptococcus mutans biofilm. (11th January 2019) - Chen, Zhao; Yang, Guang; Lu, Shengsheng; Chen, Daiwei; Fan, Sheng; Xu, Junyang; Wu, Buling; He, Jian
Abstract: Dental plaque is closely related to the occurrence of dental caries, of which the main causative bacterium is Streptococcus mutans ( S. mutans ). In this study, to create potent antibiofilm agents, we chose a human antimicrobial peptide LL‐37 as our starting material and modified it by cutting it shorter and varying its charge and hydrophobicity. The results of anti‐ S. mutans as well as biofilm inhibitory activity tests indicated that two derivatives, IG ‐13‐1 andIG‐13‐2, were the most potent one toward both planktonic and biofilm S. mutans cells with the minimal inhibitory concentration of 5.0 μM and minimal biofilm inhibitory concentrations of 5.91 ± 0.91 μM and 7.58 ± 0.23 μM, respectively. The modes of action study showed thatIG ‐13‐1 andIG‐13‐2 were functioned by disrupting the bacterial membrane, causing the leakage of inner contents, thereby leading to the death of bacterial cells eventually. In addition, IG ‐13‐1 andIG‐13‐2 were able to suppress the expression of proinflammatory cytokine of TNF‐α and reduce the level of nuclear transcription factor‐κB, which indicated the potential anti‐inflammatory activity of these peptides. Conclusively, this study indicated thatIG‐13‐1 andIG‐13‐2 are potent peptides in both anti‐ S. mutans and anti‐inflammatory activities, therefore, showing a potential application for the prevention and treatment of dental caries. Abstract : This study indicates thatIG‐13‐1 andIG‐13‐2 are potent antimicrobial peptides in inhibiting the growth of Streptococcus mutans and the formation of its biofilm. The modes of action of these peptides are involved with the interaction with the bacterial membrane which led to the disruption of the integrity of cell membrane. Therefore, IG‐13‐1 andIG‐13‐2 show a potential application for the prevention and treatment of dental caries.